Study on factor and criteria to select the ideal hydrology station - Siti Marini , Saat (2013)
Hydrology is often defined as a science dealing with the properties, distribution, and circulation of water. The purpose of hydrologic study is to determine the type and amount of hydrologic data needed. To collect the data, the hydrology stations need to be select before doing the fieldwork. The physical criteria of the hydrology station will affect the result of the research. The objective of this study is to identify the factor and criteria to select the ideal hydrology station for water discharge station and water quality station. The impact of the unfulfilled criteria of the hydrology station to the water flow and selected water quality's parameters will be det$mined. The parameter that will be test on this study is water flow rate, Q (m 3 /s), total suspended solid, TSS (mgIL), chemical oxygen demand, COD (mgIL), and biochemical oxygen demand, BOD (mg/L). Three factors involve in this study are; i) river features, ii) existing of obstruction on the water flow and iii) the distance between two hydrology station. Velocity area method is used to determine the total flow rate. For this study, Sungai Galing Besar has been chosen as a study area. This study shows that unfulfilled criteria of the hydrology station give effect to the selected parameter's reading. The result at the station of curved stream shows the velocity become lower and the TSS, COD and BOD reading will increase. At the station that having the obstruction on water flow, the velocity are increase because of the cross section area are decrease. The longest distance between two hydrology stations give the readings of the parameter are more different. For the medium distance, the difference reading is about average. While for the short distance, the difference reading is too small. From the result, the medium distance is acceptable as the distance between two hydrology stations. So that, the criteria of hydrology station need to be consider before conduct the hydrology study to obtain the accurate result.